2012
DOI: 10.1080/02786826.2012.708947
|View full text |Cite
|
Sign up to set email alerts
|

An Apparatus for Generating Aged Cigarette Smoke for Controlled Human Exposure Studies

Abstract: Research has shown that cigarette smoke changes chemically and physically after it is released into indoor air, that these changes can increase secondhand smoke (SHS) toxicity, and that acute exposures to even low levels of SHS increase the risk of cardiopulmonary disease. We designed a system to reproduce realistic SHS exposures in the laboratory for use in controlled human exposure studies. We generated cigarette smoke with a smoking machine, diluted it and conducted it through a 6 m 3 stainless steel flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 28 publications
(37 reference statements)
2
31
0
Order By: Relevance
“…The smoke aging system is described in detail in Schick and Farraro et al 26. Briefly, smoke generated by an automatic smoking machine (Model TE-10z, Teague Enterprises, Woodland, California, USA) was diluted into conditioned, filtered air, and conducted through a 6 m 3 stainless steel aging chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The smoke aging system is described in detail in Schick and Farraro et al 26. Briefly, smoke generated by an automatic smoking machine (Model TE-10z, Teague Enterprises, Woodland, California, USA) was diluted into conditioned, filtered air, and conducted through a 6 m 3 stainless steel aging chamber.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that there are significantly higher levels of the tobacco-specific nitrosamine NNK in SHS. Previous studies showed that the ratio of NNK:nicotine in the aged smoke aerosol generated in our lab is approximately 4 × 10 −4 (Schick et al, 2012a). The ratio of NNK:nicotine in fresh mainstream smoke is approximately 2 × 10 −6 and in fresh sidestream smoke it is approximately 1×10 −4 (IARC Working Group on the Evaluation of Carcinogenic Risks to Humans and World Health Organization, 2004).…”
Section: Biomarkers Of Shs Exposurementioning
confidence: 97%
“…Subjects were exposed to aged cigarette smoke generated in a custom-built system in the lab (Schick et al, 2012a). Cigarette smoke was generated with a smoking machine (TE10z, Teague Enterprises, Woodland, CA), diluted with conditioned, filtered air,and conducted through a large flow reactor at rates equivalent to the upper ranges of normal residential air exchange rates, creating aged cigarette smoke as a model for SHS.…”
Section: Smoke Exposuresmentioning
confidence: 99%
“…In one study with cigarette smoke, particle deposition to chamber walls ranged from 23 % to 78 %, which is dependent on the wall material and independent of particle concentration and flow rate (Schick et al, 2012). Other studies 350 simulated the chamber wall loss of particles and vapors from BB smoke (Bian et al, 2015;Trump et al, 2016).…”
Section: Particle Wall Loss Rate and Shift In Size Distributionmentioning
confidence: 99%
“…Smog chambers (both indoor and outdoor) have been used, beginning in the 1960s, to study atmospheric processes in controlled environments, such as biomass burning emissions (Kamens et al, 1984;Hennigan et al, 2011;Bian et al, 2015), SOA production (Carter et al, 2005;Babar et al, 2016), diesel exhaust (Weitkamp et al, 85 2007), and cigarette smoke (Schick et al, 2012). As opposed to in situ measurements, the aging process can be studied over longer times in a chamber with greater temporal accuracy and sampling frequency.…”
mentioning
confidence: 99%